Potensi Eugenol Fraksi Etil Asetat Bunga Cengkeh terhadap Proliferasi Kanker Serviks (HeLa Cell Line) - Pratama, Fajri Rahendra; Sari, Annisa Permata; Susanti, Aprilia; Syakira, Hasya; Salsabila, Amilia; Arisanty, Dessy (Fakultas Kedokteran, Universitas Andalas, 2024)
Cervix cancer, also known as cervical cancer, is a type of cancer that is caused mainly by oncogenic Human Papillomavirus (HPV), which attacks the cervix. One of the plants that can be used in medicine is clove. Objective: To analyzed the effect of a fraction of ethyl acetate eugenol of clove flower for the proliferation and migration of HeLa cells. Methods: This was an in vitro experiment. Ethyl acetate fraction was tested in vitro with the MTT Assay method. A scratch Assay is done to determine the migratory power of cancer cells to Trypan Blue to see (dead cells/living cells). Data collection techniques were carried out using experimental observation techniques. The data obtained in the MTT test is the percentage of inhibited HeLa cells. Scratch Assay results were analyzed with ImageJ software and the Trypan Blue method using the TC10 tool. Results: The MTT Assay test obtained an IC50 value of 24.51 µg/ml, the average migration of treatment cells 303 and the average control group 715 cells. The number of proliferating treatments 6.14 x 105 and control 12.1 x 105. Conclusion: Based on its potential, clove flower can be a candidate for cervical cancer cell therapy (HeLa Cell Line) in the future.Keywords: anti-cervical cancer, cervical cancer, cell proliferation, MTT assay, scratch assay